Analysis of The Reading Comprehension Abilities of Fifth Grade Students in Indonesian Language Learning using The Problem Based Learning Model - Rahma Putri Octavianti; Widia Nur Jannah; Hanikah (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2025)
This research analyzes the implementation of the Problem-Based Learning (PBL) model and its impact on fifth-grade students’ short story reading comprehension at SDN 1 Arjawinangun. The study responds to challenges such as low reading interest and difficulty in understanding text content. Grounded in constructivist theory (Piaget & Vygotsky), social learning theory (Bandura), and metacognitive theory (Flavell), PBL encourages active, meaningful, and reflective learning. This qualitative case study involved a teacher and selected fifth-grade students, using interviews, participatory observation, and document analysis as data collection techniques. The findings show that PBL was effectively implemented through stages of problem orientation, organizing learning, guiding investigation, creating and presenting work, and evaluating the process. This approach significantly improved students’ comprehension skills, including identifying characters, determining main ideas, extracting moral values, and concluding story content. Students showed increased interest and motivation due to the interactive nature of PBL, which aligns with meaningful learning theory (Ausubel). Both teacher and students perceived the model positively, recognizing it as innovative and supportive in enhancing text comprehension. Although challenges such as time constraints and adapting materials for lower-ability learners emerged, the study concludes that PBL is a theoretically sound and practically effective strategy to enhance reading comprehension in elementary education.